The development of my course file: A contribution to the digital database management system at Universiti Malaysia Sabah - Amina Ali; Sabariah Sharif; Mad Noor Madjapuni; Asmaa AlSaqqaf; Romzi Ationg; Aishah Tamby Omar; Saifulazry Mokhtar; Nor Dawirah Rahman; Chee Shiaw Phin (Primrose Hall Publishing Group, 2025)
This study aims to introduce my course file as a digital course file database management system at the Centre for the Promotion of Knowledge and Language Learning (CPKLL), Universiti Malaysia Sabah (UMS). My course file was developed to help the Centre in managing and handling course files digitally. This innovative solution enhances departmental efficiency and significantly benefits all parties. It aligns with e-government towards the goals of the Fourth Industrial Revolution (IR4.0), empowering educational institutions through the digital transformation of course files. This study employs Design and Development Research (DDR) and qualitative research methods. A mixed-method approach was adopted to incorporate user feedback, which is essential for assessing the products or systems' usefulness, particularly for UMS. The unique feature of my course file is its ability to provide a digital database management system equivalent to an existing system. As technology evolves, the importance of digital literacy in educational information systems becomes increasingly crucial. This study highlights the courage to develop large databases, which is a rare study. The fact that only a small number of educational institutions are moving forward with digital course file development proves the advancement of this educational management system.